A possibilidade de barganha coletiva nas relações econômicas desiguais no Sistema Brasileiro de Defesa “Econômica” à luz da tese do poder compensatório - Alexandre Cordeiro Macedo (2022)
This work focuses on the thesis of countervailing power, based especially on economist John Kenneth Galbraith’s works, and examines its role in collective bargaining in unequal economic relations in the Brazilian System of Economic Defense, using various methods. Firstly, we carry out an exploratory and normative bibliographic study, building a solid conceptual framework about Economic Law, Antitrust Law and countervailing power, and we analyze the economic effect of the formation of countervailing power in different market conditions. We observe the possibility of the existence of social benefits arising from a collaboration between competitors with the objective of rebalancing the links in the production chain, mitigating the exercise of market power, reducing inequalities in commercial relations and increasing social well-being, in natural response to the concentration of the original market. Compensatory power emerges as the neutralization of one power position by another, being a different mechanism from competition and regulation by the State. Through different approaches to the analysis of the competition offense, we observe the countervailing power in North American and European experiences, comparing them with Brazilian experience. Then, we focus our investigation on the Brazilian scenario, through the analysis of the jurisprudence of the Administrative Council for Economic Defense, through selection and analysis of relevant cases. We do this by examining both cases of general themes and focusing on the theme of the supplementary health market, due to its peculiarities and the characteristic asymmetry of power existing between the economic agents involved. We then proceed to analyze the effectiveness of antitrust intervention in cases of collective bargaining in the Australian normative and jurisprudential contexts, given the maturity and bold model adopted by the Australian Competition & Consumer Commission. Finally, we present the proposal to introduce notification – one of the procedures adopted by the Australian authority – to the Brazilian system, due to its limited subjective scope and its potential to allow coordination between competitors to carry out collective bargains that, based on in the countervailing power thesis, have a positive net effect on competition.